Production of Autoreactive Heavy Chain-Only Antibodies in Systemic Lupus Erythematosus - Xu, Shu; Yang, Hong; Zhuo, Yue; Yu, Yangsheng; Liao, Hongyan; Li, Song; Yue, Yinshi; Su, Kaihong; Zhang, Zhixin (Frontiers in Immunology, 2020)
Systemic lupus erythematosus (SLE) is characterized by the overproduction of high-affinity autoreactive antibodies. Here, we show that more than 65.8% of 222 recombinant antibodies derived from 8 SLE patients can be secreted as heavy chain-only antibodies (HCAbs) when expressed in HEK-293T cells. The secretion of HCAbs follows the conventional endoplasmic reticulum-Golgi apparatus pathway, despite triggering a weaker unfolded protein response (UPR). Many of the purified SLE HCAbs remain autoreactive and have an even higher affinity for dsDNA, Sm, nucleosome, and cardiolipin than HCAbs from healthy individuals. Extended analyses of the CDR3 region and the heavy chain variable (VH) region of HCAb F3 show that the VH region is responsible for IgH secretion, while the CDR3 region determines its reactivity. Such a high frequency of HCAb secretion cannot fully concur with our current understanding of antibody assembly and secretion. The presence of a large proportion of autoreactive HCAbs in SLE reveals a novel mechanism for the generation of autoreactive antibodies in lupus.